Development and Validation of Physics Learning Motivation Survey (PLMS) using Rasch Analysis - Judyanto Sirait (Postgraduate, University of Mataram, 2023)
Motivation can affect the success of students’ learning. Teachers need a valid instrument to measure students’ motivation while learning physis. This study aims to describe the process of developing and validating of physics learning motivation survey (PLMS) for senior high school. Research and development approach is implemented in this study by following stages: define, design, develop, and disseminate. In the previous study, the survey has been generated 40 items with eight factors including teachers’ factor, carrier plan, learning strategy, self-efficacy, instructional media, learning environment, learning interest, and online/offline instruction. The present study is to validate empirically the survey using Rach analysis by involving 947 senior high school students in Kalimantan Barat. The results from Rach analysis show that 35 items are acceptable which have infit and outfit mean square value from 0.5 to 1.5 logits. Then item reliability and person reliability are 0.99 and 0.91 respectively. This indicates that the PLMS is valid and reliable to measure students’ motivation in learning physics